Penerapan Absen Elektronik Sikepo Dalam Meningkatkan Disiplin Serta Pengaruhnya Terhadap Kinerja Pegawai Pada Dinas Perumahan dan Kawasan Pemukiman Kabupaten Batang Hari - Etty Siswati; Evi Fauzani (CITRA EKONOMI, 2020)
This study aims to study the role of the Sikepo electronic absence in the Department of Housing andHousing Area (X) Work Discipline in the Of ice of Housing and Settlement Areas of Batang HariRegency on (Y) Performance of Employees in Housing and Settlement Areas of Batang Hari Regency. This research is a quantitative descriptive study. The population of this study was 44 people. Based onthe results of research and discussion, then several research subjects can be given as follow. The resultsof the t-test obtained (X) = 6,781> 1.68195. then Ha is rejected and Ho is accepted because tcount isgreater than ttable. R Square value of .52,3 Thus the whole can be concluded as a Disciplinary Variable(X) variable against Employee Performance variable (Y) in the housing service and residential area ofBatang Hari Regency, respectively by 52.3% and 47.7% Research by other variables discussed in thisstudy.